Shrimp oral immunotherapy outcomes in the phase 2 clinical trial: MOTIF - Jiang, Shirley Y.; Cao, Shu; Martinez, Kristine; Sharma, Reyna; Raeber, Olivia; Fernandes, Andrea; Bogetic, Dinara; Kaushik, Abhinav; Gupta, Sheena; Manohar, Monali; Maeker, Holden T.; Chin, Andrew R.; et al. (Frontiers in Allergy, 2025)
IntroductionShrimp is a common but understudied food allergen with relatively high rates of emergency department visits. Here we report the shrimp OIT outcomes in the MOTIF (NCT03504774) clinical trial and discuss some of the challenges with performing this study.MethodsIn this phase 2 clinical trial, 12 shrimp allergic participants aged 7–55 years (median age 21.5 years) were enrolled to receive shrimp OIT. Shrimp OIT was performed up to a maintenance dose of 1,000 mg shrimp protein by week 28 with desensitization to shrimp assessed by double-blind placebo-controlled food challenge at week 52 followed by switching to avoidance and assessing sustained unresponsiveness (SU) at week 58. The primary endpoint was the change in CD28 in CD4+ allergen specific (CD154+) T-cells at baseline and 52 weeks.ResultsShrimp OIT induced desensitization to a cumulative 4,043 mg shrimp protein in 58.3% (7/12) of the intention to treat and 87.5% (7/8) of the per protocol group after 52 weeks of shrimp OIT. Most shrimp OIT participants who remained in the study after desensitization (87.5%, 7/8) achieved SU. Although adverse events were common during shrimp OIT (75%), most were mild (Bock grade 1, 88%) and there were no severe (Bock grade 3+) reactions or use of epinephrine. No significant differences in CD28 expression were observed after shrimp OIT.ConclusionsShrimp OIT is safe and effective for the treatment of shrimp allergy. Most participants were successful and achieved SU after 6 weeks of avoidance.